BODIPY Dyes A Privilege Molecular Scaffold with Tunable Properties - Bañuelos-Prieto, Jorge; Sola Llano, Rebeca (IntechOpen, 2019)
Nowadays, dye chemistry is a booming area of research. In particular, BODIPY fluorophore dyes are in the spotlight since their chromophore allows the design of tailor-made molecules for specific (bio)technological purposes. BODIPY Dyes: A Privilege Molecular Scaffold with Tunable Properties aims to highlight such chemical versatility and modulable photophysical and electrochemical properties. The second and the third chapter deal with BODIPYs in chemosensing and as labels for bioimaging. The fourth chapter focuses on their electroluminescence and redox properties, and their role in photocatalysis. The fifth chapter provides deeper insight into the degradation mechanisms in acid and basic media. The book aims to overview the state of the art of BODIPYs and inspire readers involved in dye chemistry.